Marjolin's ulcer in two horses with hereditary equine regional dermal asthenia - Badial, Peres R. [UNESP] (2013)
Two Quarter Horse mares with hereditary equine regional dermal asthenia (HERDA) were diagnosed with metastatic squamous cell carcinoma (SCC) associated with chronic nonhealing wounds. The lesions were similar to the development of SCC from chronic nonhealing ulcers, known as Marjolin's ulcers in humans. The horses showed recurrent skin wounds in the saddle and paralumbar regions and were confirmed by molecular techniques as having HERDA. Both horses were maintained as research animals for prolonged periods and received regular veterinary care and wound treatment. Both horses were ultimately euthanized because of their chronic progressive wounds, coupled with declining health. At necropsy, the nonhealing wounds were found to be complicated by infiltrative SCC; both horses had metastasis to lungs. Chronically inflamed, recurrent skin wounds that heal slowly and incompletely as a consequence of HERDA are proposed as a major pathogenetic factor in tumorigenesis. Consistent findings with respect to proliferation index (Ki-67) and mutations of p53 tumor suppressor gene were confirmed by immunohistochemistry in one horse. SCC consistent with Marjolin's ulcer has been previously suggested in association with chronic ulcers or burn scars in horses, but this is the first report of an association with chronic poor healing wounds in HERDA horses. © 2013 Elsevier Inc.